System of six-level atom interacting with a quantized field in the existence of time-varying coupling - Mariam Algarni; Kamal Berrada; Sayed Abdel-Khalek; Hichem Eleuch (Results in Physics, 2023)
In the present manuscript, we extend the Jaynes-Cummings model in the framework of six-level atom (LA) system in the presence of a quantized field describes by an ordinary coherent state or a superposition state. We investigate the dynamics of the population, coherence and quantum entanglement in terms of the system parameters. We analyze the time variation of the quantifiers in the presence and absence of time-varying coupling of the six-LA–field system and make comparison among the quantifiers. Furthermore, we show how the quantifiers can be controlled according to the values of the system parameters. The obtained results illustrate that the proposed system provides interesting values of the quantum coherence and entanglement which can be considered as good candidates for executing quantum optics and information schemes.